International property law - Tatar, Olga (Print-Caro, 2023)
Property law is a set of legal rules governing such property relations in which authorized persons can exercise their rights to property (things) without the need for positive actions of other persons. The acquisition and termination of ownership and other real rights to property are determined by the law of the state in whose territory the property was located or was located at the time of the action. The signs of property rights are: a) Property rights are provided for by civil law. b) The right in rem is an absolute right, namely, in the event of a collision between its owner and an unlimited number of subjects on whom the obligation is assigned, the rights of the bearer of the right in rem are not violated. c) The right of ownership accompanies a thing as a result of its transfer to other persons, the so-called right of inheritance. If the owner of a thing withdraws from possession of the thing against his will, he still remains the owner and is not even deprived of the right to reclaim the thing from someone else’s illegal possession. d) Property rights are preferential rights; in case of contradictions between property and liability rights, priority will be on the side of property rights. e) The object of property rights are individually defined things. The central institution of property law is the right of ownership. The legal content of property relations is manifested through a set of subjective exclusive rights of the owner, through the triad of the following components: possession, use and disposal. The owner of a thing has the right to dispose of the thing at his own discretion and not to allow any influence on the thing by other persons.

Dreptul proprietății este un set de reguli juridice care reglementează astfel de relații de proprietate în care persoanele autorizate își pot exercita drepturile asupra proprietății (lucrurilor) fără a fi nevoie de acțiuni pozitive ale altor persoane. Dobândirea și încetarea dreptului de proprietate și a altor drepturi reale de proprietate sunt determinate de legea statului pe teritoriul căruia imobilul se afla sau se afla la momentul acțiunii. Semnele dreptului de proprietate sunt: a) Drepturile de proprietate sunt prevăzute de legea civilă. b) Dreptul real este un drept absolut, și anume, în cazul unei coliziuni între titularul său și un număr nelimitat de subiecți cărora li se cede obligația, drepturile titularului dreptului real nu sunt încălcate. c) Dreptul de proprietate însoţeşte un lucru ca urmare a transmiterii acestuia către alte persoane, aşa-zisul drept de moştenire. Dacă proprietarul unui lucru se retrage din posesia lucrului împotriva voinței sale, el rămâne totuși proprietar și nici măcar nu este lipsit de dreptul de a revendica lucrul din posesia ilegală a altcuiva. d) Drepturile de proprietate sunt drepturi preferenţiale; în caz de contradicții între drepturile de proprietate și cele de răspundere, prioritate va fi de partea drepturilor de proprietate. e) Obiectul drepturilor de proprietate sunt lucruri definite individual. Instituția centrală a dreptului proprietății este dreptul de proprietate. Conţinutul juridic al raporturilor de proprietate se manifestă printr-un ansamblu de drepturi subiective exclusive ale proprietarului, prin triada următoarelor componente: deţinerea, folosirea şi înstrăinarea. Proprietarul unui lucru are dreptul de a dispune de lucru la propria discreție și de a nu permite vreo influență asupra lucrului de către alte persoane.
DREPTUL INTERNAȚIONAL AL PROPRIETĂȚII
Keywords: property law; property relations; acquisition and termination of property rights; obligations; subjects; individual thing; priority; dreptul proprietăţii; raporturile de proprietate; dobândirea şi încetarea drepturilor de proprietate; obligaţii; subiecte; lucru individual; prioritate